Comparative Study of Two Monoterpenes Effect on Rhipicephalus microplus Tick - Coulibaly, Anass; Hema, Delphine M.; Kiendrebeogo, Martin; Nebie, Roger C.H. (European Scientific Journal, ESJ, 2023)
The cattle tick Rhipicephalus microplus is one of the most important ectoparasites for livestock in tropical and subtropical areas worldwide. This tick hurts the economy of the milk and meat production chain. In addition, it constitutes a vector for the transmission of Anaplasmosis and Babesiosis pathogens. The control of R. microplus populations is mainly based on the use of synthetic acaricides. However, using this control method presents a danger to humans and the environment and leads to the emergence of resistant tick populations. In this situation, searching for ecological and effective control alternatives is essential. Thus, plant extracts constitute a promising solution, particularly essential oils and their active compounds. Thus, the present study aims to assess the acaricidal activity of two monoterpenes (Thymol and 1.8 cineole) abundantly found in essential oils to find an alternative to synthetic acaricides. The acaricidal activity was determined according to the method of larval immersion test (LIT). Eight concentrations were tested and R software version 4.0.3 was used for data analysis. Results showed 100 % larval mortality rates for the two monoterpenes with LC50 and LC90 values of (0.28 and 0.64) and (0.64 and 2.66) respectively, for thymol and 1.8 cineole for the immersion time of 5 min. For 10 min of immersion, all LC values decreased for the two monoterpenes. These findings highlight the potential of the thymol and 1.8 cineole as an alternative for managing R. microplus tick.